2022
DOI: 10.1186/s13071-022-05358-9
|View full text |Cite
|
Sign up to set email alerts
|

A fat body transcriptome analysis of the immune responses of Rhodnius prolixus to artificial infections with bacteria

Abstract: Background Rhodnius prolixus is an important vector of Trypanosoma cruzi, the causal agent of Chagas disease in humans. Despite the medical importance of this and other triatomine vectors, the study of their immune responses has been limited to a few molecular pathways and processes. Insect immunity studies were first described for holometabolous insects such as Drosophila melanogaster, and it was assumed that their immune responses were conserved in all insects. However, study of the immune re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 104 publications
(191 reference statements)
0
4
1
Order By: Relevance
“…In this study, defensins and prolixicins were among the most highly up-regulated genes in the midgut, with defensins reaching a log2 fold expression level change of 9. Notably, this level surpasses that reported in comparable studies with kissing bugs, mosquitoes, and vinegar flies, where defensins did not appear to be as highly up-regulated ( 5 , 6 , 9 , 70 , 79 85 ). These different levels of expression warrant further exploration.…”
Section: Resultscontrasting
confidence: 62%
See 1 more Smart Citation
“…In this study, defensins and prolixicins were among the most highly up-regulated genes in the midgut, with defensins reaching a log2 fold expression level change of 9. Notably, this level surpasses that reported in comparable studies with kissing bugs, mosquitoes, and vinegar flies, where defensins did not appear to be as highly up-regulated ( 5 , 6 , 9 , 70 , 79 85 ). These different levels of expression warrant further exploration.…”
Section: Resultscontrasting
confidence: 62%
“…They orchestrate cell fate, recycle cellular components, silence foreign nucleic acids, facilitate immune signaling, adapt to environmental challenges, and serve innate immunity roles, thereby ensuring that insects effectively manage infections and maintain resilience against pathogens. The specific genes underlying these immune responses in bed bugs remain unexplored ( 5 , 22 , 33 , 35 , 44 , 86 , 87 , 89 ). We investigated gene regulatory patterns associated with apoptosis and the cysteinyl aspartate protease (CASP) gene families, as well as cellular processes including autophagy, RNAi pathways, serine proteinases, stress responses, and TEPs in both the midgut and RoB following ingestion of bacteria (refer to Supplementary Table S4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, silencing of the Dorsal gene, the transcription factor of the Toll pathway, also does not alter T. cruzi infection (Figure 1F) (Mesquita et al, 2015). Years later, Salcedo-Porras et al ( 2019) identified additional components of the R. prolixus IMD pathway using reciprocal BLAST and HMM profile searches (Salcedo-Porras et al, 2019).…”
Section: Kissing Bugs and Trypanosoma Cruzi: A Pathogen Adapted To Di...mentioning
confidence: 90%
“…The insect effector immune factors include antibacterial peptides (AMPs), lectins, prophenoloxidases (PPOs, for melanisation), reactive oxygen species (ROS), nitric oxide (NO), antiviral factors, cytokines and many more [ 17 , 68 , 69 ]. Much of the knowledge of these processes was gleaned by work on Drosophila [ 70 , 71 , 72 ] while valuable contributions have also been made with other species including Aedes/Anopheles mosquitoes [ 18 , 29 , 73 , 74 , 75 ], Hyalophia cecropia [ 76 ], Manduca [ 77 , 78 ], Galleria [ 79 , 80 , 81 ] and Bombyx [ 82 , 83 ] moths, Sarcophaga fleshflies [ 84 , 85 ] and Rhodnius assassin bugs [ 86 , 87 ].…”
Section: Typical Insect Immune Scenariomentioning
confidence: 99%